Two Decades of Indonesia’s Democracy and the Fading of Feminist Agenda - Anna Margret (Jurnal Perempuan, 2019)
This article explores the complexity of the relationship between democracy and feminism in both theory and practice. For a long time, feminist theorists have put forward criticism of democratic studies, which emphasize the importance of transforming political institutions and addressing the measure of the goodness of democracy that is considered to be generally accepted. As a result, the voice and interests of women are considered merely complementary and not a priority. Feminist agendas—marked by the formulation of interests aimed at challenging patriarchy in a variety of manifestations—are increasingly scarce in the work of fighting for democracy in Indonesia, especially in the participation of women’s electoral politics. While non-electoral participation is more indicative of the presence of a feminist agenda, the challenge lies in the lack of linkages with electoral politics. The achievements of democracy over the past 20 years show the lack of contribution of democracy to the struggle that the women’s movement formulated with the breath of feminism. This article highlights the increasingly eroded feminist agenda in the consolidation of democracy in Indonesia. It is time for the consolidation of democracy to borrow the logic of feminism, which rejects the public/private; personal/political dichotomy; in the electoral/non-electoral political struggle.